Guanxin Danshen Formulation Protects against Myocardial Ischemia Reperfusion Injury-Induced Left Ventricular Remodeling by Upregulating Estrogen Receptor β - Deng, Xuehong; Xing, Xiaoyan; Sun, Guibo; Xu, Xudong; Wu, Haifeng; Li, Guang; Sun, Xiaobo (Frontiers in Pharmacology, 2017)
Background: Guanxin Danshen formulation (GXDSF) is a traditional Chinese herbal recipe recorded in the Chinese Pharmacopoeia since 1995 edition, which consists of Salviae miltiorrhizae Radix et Rhizoma, Notoginseng Radix et Rhizoma and Dalbergiae odoriferae Lignum. Our previous research suggested GXDSF had positive effect on cardiovascular disease. Therefore, the aim of this study was to elucidate the effects of GXDSF on myocardial ischemia reperfusion injury-induced left ventricular remodelling (MIRI-LVR). Methods: The effects of GXDSF on cardiac function were detected by haemodynamics and echocardiograms. The effects of GXDSF on biochemical parameters (AST, LDH and CK-MB) were analysed. Histopathologic examinations were performed to evaluate the effect of GXDSF on cardiac structure. In addition, the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database was used to predict the main target of GXDSF. Target validation was conducted by using western blots and immunofluorescent double staining assays. Results: We found that +dp/dt and LVSP were significantly elevated in the GXDSF-treated groups compared with the MIRI-LVR model group. Left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS) were increased in the GXDSF-treated groups compared with the model group. All biochemical parameters (AST, LDH and CK-MB) were considerably decreased in the GXDSF-treated groups compared with the model group. Fibrosis parameters (collagen I and III, α-SMA, and left ventricular fibrosis percentage) were decreased to different degrees in the GXDSF-treated groups compared with the model group, and the collagen III/I ratio was elevated by the same treatments. TCMSP database prediction and western blot results indicated that estrogen receptor β (ERβ) could be the main target of GXDSF. PHTPP, a selective antagonist of ERβ, could inhibit the expression of ERβ and the phosphorylation of PI3K and Akt in myocardial tissue induced by GXDSF, and partly normalize the improving effects of GXDSF on +dp/dt, LVEF, LVFS, LDH, CK-MB, α-SMA and myocardial fibrosis. Conclusion: Collectively, GXDSF showed therapeutic potential for use in the prevention and treatment of myocardial ischemia reperfusion injury-induced ventricular remodelling by upregulating ERβ via PI3K/Akt signalling. Moreover, these findings may be valuable in understand the mechanism of disease and provide a potential therapy of MIRI-IVR.